EVALUATION OF SODIUM BENTONITE EFFECTS ON AFLATOXIN B1 TOXICITY: IN VITRO STUDY: EVALUATION OF SODIUM BENTONITE EFFECTS ON AFLATOXIN B1 TOXICITY: IN VITRO STUDY (Iraqi Journal of Market Research and Consumer Protection, 2025)
The study aimed to investigate the impact of different concentrations of aflatoxin B1 in concentrated animal feeds on the digestion of dry matter and organic matter, as well as the production of greenhouse gases (total gas and methane) after 24 hours of digestion in a laboratory setting. To mitigate the negative effects of aflatoxin, various proportions of sodium bentonite clay (SB) were added. Four treatments were prepared and labeled as T1, T2, T3, and T4, with varying concentrations of aflatoxin (0, 20, 40, and 60 parts per billion, respectively). Different percentages of sodium bentonite clay (0%, 3%, 5%, and 7%) were added to each treatment. Statistical analysis revealed significant increases (P˂0.05) in the values of dry matter digestion among the different treatments. T1 recorded the highest value (84.09), while T4 had the lowest (65.08) at a concentration of 0%. Similar trends were observed in organic matter digestion, with T1 showing the highest value (92.38), and T4 the lowest (78.54) at 0% concentration. The addition of 7% sodium bentonite clay resulted in the highest digestion rate (89.26), followed by 5% (88.45), 3% (87.21), and 0% (84.29). Regarding total gas production after 24 hours, significant increases were observed (P˂0.05) among the different treatments. T1 had the highest value (45.66), while T4 had the lowest (15.66) at a concentration of 0%.In summary The study showed that adding sodium bentonite clay to concentrated animal feed resulted in a partially reduction of the negative effects of aflatoxin B1, leads to improved bacterial digestion through laboratory digestion.